The Effect of Administrative Development, Training and Human Capital on Syrian Economic Foundations - Mille, Assad; cheikh Ibrahim, Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper is concerned with shedding lights on major internal and external variables related to status quo of Syrian economic foundations in addition to the importance of investing in human capital, which is considered a real measure of management's ability to succeed in achieving objectives through organizing, developing and completing training programs for human resources, it also implies how progressive an administrative mentality and development in these organizations.